The individual and the common in folkloric semantic models: an attempt at contemporary folklore analysis - Лабащук, Oксана (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
Structural and semantic study of contemporary oral tradition reveals in the individual studies about the personal experience of pregnancy and childbirth the phenomena of schematization and repetition. This can be seen as a key element in the analysis of modern natal narratives. Certain motives accumulate traditional folkloric and mythological semantics.